2017
DOI: 10.1159/000479865
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Cytomegalovirus Infection during Exacerbation of Ulcerative Colitis

Abstract: Background/Aims: The role of cytomegalovirus (CMV) reactivation during exacerbations of ulcerative colitis (UC) is yet a matter of debate, and assessment of CMV infection in UC patients remains an ongoing challenge. We aimed to identify associated parameters and compare detection methods for CMV infection during UC exacerbation. Methods: Clinical, pathological and virological parameters were retrospectively analyzed in all patients hospitalized in our institution for UC exacerbation between January 2009 and Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The CMV seroprevalence analysis in adults showed at least 70% of seropositivity [ 28 , 29 ]. At the endoscopy, the only factor that may suggest the diagnosis is the presence of ulcerations with a well-defined, punched-out appearance present in up to 80% of patients [ 30 32 ]. Some studies proposed a typical cecum ulcer involving the ileocecal valve as a specific finding in CMV colitis in patients with graft-versus-host disease [ 33 ].…”
Section: Specific Acute Abdominal Infections In Immunocompromised Patientmentioning
confidence: 99%
“…The CMV seroprevalence analysis in adults showed at least 70% of seropositivity [ 28 , 29 ]. At the endoscopy, the only factor that may suggest the diagnosis is the presence of ulcerations with a well-defined, punched-out appearance present in up to 80% of patients [ 30 32 ]. Some studies proposed a typical cecum ulcer involving the ileocecal valve as a specific finding in CMV colitis in patients with graft-versus-host disease [ 33 ].…”
Section: Specific Acute Abdominal Infections In Immunocompromised Patientmentioning
confidence: 99%
“…Another 22 articles were further excluded by reading the full text. Ultimately, 20 [9,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] articles were eligible for data extraction and meta-analysis. The searching process is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…Furthermore, patients with CMV infection showed lower serum albumin levels, which was probably due to sever inflammatory process (present as high hsCRP levels) and insufficient intake. A few studies [31,33,34] have indicated that albumin is a nutritional and inflammatory marker that reflects the potential for infection or disease activity. However, the effect of treatment targeting at increasing albumin in CMV infection has not been fully illustrate.…”
Section: Discussionmentioning
confidence: 99%